Novel Nuclear Partnering Role of EPS8 With FOXM1 in Regulating Cell Proliferation - Ngan, Adaline Wan Ling; Grace Tsui, Michelle; So, Danny Hon Fai; Leung, Wai Ying; Chan, David W.; Yao, Kwok-Ming (Frontiers in Oncology, 2019)
One hallmark of cancer cells is sustaining proliferative signaling that leads to uncontrolled cell proliferation. Both the Forkhead box (FOX) M1 transcription factor and the Epidermal Growth Factor (EGF) receptor Pathway Substrate 8 (EPS8) are known to be activated by mitogenic signaling and their levels upregulated in cancer. Well-known to regulate Rac-mediated actin remodeling at the cell cortex, EPS8 carries a nuclear localization signal but its possible nuclear role remains unclear. Here, we demonstrated interaction of FOXM1 with EPS8 in yeast two-hybrid and immunoprecipitation assays. Immunostaining revealed co-localization of the two proteins during G2/M phase of the cell cycle. EPS8 became nuclear localized when CRM1/Exportin 1-dependent nuclear export was inhibited by Leptomycin B, and a functional nuclear export signal could be identified within EPS8 using EGFP-tagging and site-directed mutagenesis. Downregulation of EPS8 using shRNAs suppressed expression of FOXM1 and the FOXM1-target CCNB1, and slowed down G2/M transition in cervical cancer cells. Chromatin immunoprecipitation analysis indicated recruitment of EPS8 to the CCNB1 and CDC25B promoters. Taken together, our findings support a novel partnering role of EPS8 with FOXM1 in the regulation of cancer cell proliferation and provides interesting insight into future design of therapeutic strategy to inhibit cancer cell proliferation.